Pengaruh Gaya Kepemimpinan Dan Beban Kerja Terhadap Kinerja Karyawan Bpjs Ketenagakerjaan Cabang Meulaboh - Ana Marliana (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2021)
In this study, high employee performance can be achieved from every element in the organization both in carrying out the role as employees who improve quality and performance according to the influence of the leadership style of a leader on employee interactions at BPJS. This research method uses quantitative data collection techniques through questionnaires on a sample of all 20 employees. From the results of multiple linear regression research shows that the variables in the study have a positive effect on employee performance. The results of the leadership style t-test are positive and have a significant effect, while workload is positive and has no significant effect on employee performance. The results of the F test show that leadership style and workload simultaneously (simultaneously) have a significant effect on employee performance. And the results of the coefficient of determination test show that 76.40% of employee performance can be influenced by leadership style and workload factors.